Central bank communication: Managing expectations through the monetary dialogue - Ansgar Belke (Research On Money in the Economy (ROME), 2017)
Successfully managing a course back to normality ("exit") will depend crucially on the central banks' ability to communicate effectively a credible strategy for an orderly exit from such kind of policies. In this context, clear, deliberate, coordinated messages that are anchored in the central banks' mandate are of essence. We focus upon transparency and "forward guidance" as potential tools to stimulate the economy in the Euro Area. We then deliver details on whether and how the effectiveness of central bank's policies can be improved through more transparency and "forward guidance". We do so by highlighting marked differences in the Fed's and the ECB's interpretation of "forward guidance". In order to highlight the key issues of central bank communication and the management of expectations referring to a practical institutional example, we also comment on the role the Monetary Dialogue in the context of an evolving monetary policy. Communication is finally described as a policy option in terms of minimising risk in the context of exit from unconventional monetary policies and of the signalling channel which refers to what the public learns from announcements of unconventional monetary policy operations such as Quantitative Easing.
Keywords: E52; E58; G14; 330; central bank communication; European Central Bank; forward guidance; monetary dialogue; transparency